Understanding the motivational mechanisms behind the usage frequency of ride-hailing during COVID-19 pandemic - Ling, Shuai; Jia, Yunqi; Yuan, Xuemin; Dong, Hongming; Zhang, Tianjing (Frontiers in Public Health, 2023)
Introduction This study aimed to explore the factors influencing people's utilization of ride-hailing services, particularly in the context of the COVID-19 pandemic. Methods A two-stage survey was conducted among the same group of passengers pre and post COVID-19 pandemic, resulting in a total of 670 valid samples. Exploratory factor analysis (EFA) was applied to the data, followed by the ordered probit and ordered logit models to identify the motivational factors behind passengers' frequency of using ride-hailing. Results The findings indicated that trust and loyalty were the most influential factors in determining passengers' frequency of using ride-hailing services. However, passengers' perception of the COVID-19 pandemic did not have a significant effect on the frequency of using ride-hailing. Discussion This research provides empirical evidence and policy implications for understanding people's usage of the ride-hailing services in the context of public-health emergency.